Alloyed CuInS2–ZnS nanorods: synthesis, structure and optical properties1. Issue 30 (14th August 2015) - Li, Jie; Kempken, Björn; Dzhagan, Volodymyr; Zahn, Dietrich R. T.; Grzelak, Justyna; Mackowski, Sebastian; Parisi, Jürgen; Kolny-Olesiak, Joanna
<x xml:space="preserve">Abstract</x> CuInS2–ZnS nanorods were synthesized via an easy up-scalable, heat-up method. Their growth process and the structural and optical properties were studied.